Threats to Peace and International Security: Asia versus West
XII, 243 p. 32 illus., 30 illus. in color.
Keywords: This book aims to analyze from a multidisciplinary perspective the current geopolitical conflict between East and West, between two differentiated and apparently conflicting cosmogonic visions. The geopolitical evolution of the current panorama seems to lead to a new world in the field of international relations, a new board played on a planetary level. Once again, bloc geopolitics can be glimpsed in the immediate future, in which the most important actors such as Russia, China, the United States of America, and the European Union are called to position themselves with respect to the territorial and strategic ambitions of the opponent. International law seems to be overwhelmed by military actions and factual pressure on the ground, while the battle of ideas extends to the technological field and cyberspace. The different origins of the authors, with extensive academic, military, police forces, and business experience undoubtedly enriches the unique perspective that this work intends toaddress, always in the attempt to enforce international law and the channels of dialogue between nations, such as the best solution to conflicts.